1991
DOI: 10.1111/j.2044-835x.1991.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Monsters, ghosts and witches: Testing the limits of the fantasy—reality distinction in young children

Abstract: Estes, Wellman & Woolley (1989) have shown that children as young as 3 years of age can distinguish between mental entities such as an image or dream of an object and a real object. Nevertheless, children often show persistent fear of imaginary creatures, particularly monsters (Jersild, 1943). To find out what conception children have of such imaginary creatures, 4‐ and 6‐year‐olds were questioned about three types of item: real items (e.g. a cup), ordinary imagined items (e.g. an image of a cup) and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
256
7
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(278 citation statements)
references
References 0 publications
10
256
7
4
Order By: Relevance
“…Past research suggests that children ages 3 -7 sometimes believe that what they have imagined may turn out to be true. For example, after pretending that there is a creature inside an empty box, children may peek into the empty box rather than an irrelevant box when left alone as if they thought the imagined creature might have crossed the boundary from pretend into real (Harris et al, 1991;Johnson & Harris, 1994). To our knowledge, no such study has been conducted with children under age 3, but it is quite possible that 2-year-olds may be credulous toward pretense transmigration as well.…”
Section: Discrepancy Between Different Behavioral Measuresmentioning
confidence: 75%
See 3 more Smart Citations
“…Past research suggests that children ages 3 -7 sometimes believe that what they have imagined may turn out to be true. For example, after pretending that there is a creature inside an empty box, children may peek into the empty box rather than an irrelevant box when left alone as if they thought the imagined creature might have crossed the boundary from pretend into real (Harris et al, 1991;Johnson & Harris, 1994). To our knowledge, no such study has been conducted with children under age 3, but it is quite possible that 2-year-olds may be credulous toward pretense transmigration as well.…”
Section: Discrepancy Between Different Behavioral Measuresmentioning
confidence: 75%
“…When left alone with the pretend box and a neutral box that was not involved in pretense, children approached the pretend box more quickly and touched and opened it more often than the neutral box. As Harris et al (1991) suggested, young children might believe that pretend entities can "transmigrate" into the real world.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Harris, Brown, Marriott, Whittall and Harmer (1991) found that 4-and 6-year-olds are capable of distinguishing between perceived objects (a perceived cup), imagined physical objects (an imagined cup) and fantastic objects (a witch flying in the sky). Five-year-olds are as good as adults are at differentiating between fantastic and real objects (Sharon and Woolley, 2003).…”
Section: Introductionmentioning
confidence: 99%